Education legislation in the context of socio-economic development and national security strategies - O. V. Grechkina; L. A. Dushakova; O. V. Shmaliy (Pravoprimenenie, 2025)
The subject of the study is the assessment of certain aspects of education legislation in the context of socio-economic development and national security strategies. Education is one of the most powerful long-term tools for socio-economic development and national security. This is due to the socio-cultural and information environment of involving government decision makers in a particular educational model. This situation calls for the formation of a regulatory framework in the field of education, which is combined with government policies. The purpose of the study is to substantiate the directions for improving the legislation on education from the point of view of establishing the formal and legal relationship of its individual provisions with state policies.Research methods: the authors use theoretical methods of formal and dialectical logic, empirical methods of comparison, description, interpretation as well as formal legal method. Results and conclusions. Legislation in the field of education does not form a clear formal and legal relationship with government policies. In this regard, education as an object of public administration and regulation needs conceptualization and system-forming strategic planning. These processes should include issues of education security as a socially significant good, socially significant service, and educational infrastructure. The system of principles of state policy and legal regulation in the field of education should be brought into line with the paradigms of strategic planning in the field of national security and socio-economic development. It is proposed to abandon the concept of "quality of education" in favor of the concept of "quality of educational activity" as more appropriate to the meaning and content of strategic planning acts. This will eliminate the need to substantiate the quality of education as a socially significant good and constitutional value, since in this case we are talking about the philosophy and axiology of education as a social phenomenon, and not about its quantitative and qualitative characteristics that can be measured. This approach will also make it possible to specify the goals and content of verification and evaluation activities in the field of education. It is advisable to differentiate the meanings of education. Education as a benefit should be positioned through the preamble to Federal Law No. 273- FZ dated December 29, 2012 "On Education in the Russian Federation", ensuring recognition of its social value and guarantee. It is necessary to substantiate the connection between education and enlightenment. The concept of enlightenment is immanent in education. At the same time, there remains the possibility of enlightenment activities outside the framework of educational programs, but not in opposition to education as a combination of training and upbringing.